Holocord Syringomyelia and Dorsal Hemangioblastoma: A Rare Association? - Arévalo-Sáenz, Alejandra; Ferrández-Pujante, Borja; Rascón-Ramírez, Fernando J. (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
Introduction: Syringomyelia is a neurological disease characterized by the presence of fluid-filled cavities within the spinal cord, resulting in progressive neurological deficits. Intramedullary hemangioblastomas are often accompanied by syringomyelia. However, holochordial syringomyelia is rare. The most common cause of syringomyelia remains Chiari disease, and only 10 cases of hemangioblastomas with holochordial syringomyelia have been described so far. Case Report: A case of a 35-year-old patient with a two-month history of cervicobrachialgia at the C7-C8 root level, previously preceded by pain at the D1-D2 level, has been presented. Cervico-dorso-lumbar MRI revealed a medullar tumor with an uptake mural nodule at the conus medullaris level accompanied by an extensive syringomyelic cavity from C5 to L1 compatible with medullary hemangioblastoma. The patient underwent surgery for tumor resection with subsequent resolution of her painful symptoms. Syringomyelia is mainly associated with Chiari malformation and also with inflammatory pathologies, spinal attacks, trauma, and intramedullary tumors of the spinal cord. Conclusion: The management of holochordal syringomyelia can be a great challenge. It is important to emphasize that surgical treatment is aimed at treating the origin of this syringomyelia and not the syringomyelia itself. It is mandatory to rule out the existence of Chiari syndrome as a first possibility, without forgetting the possibility of focal intramedullary spinal tumors as a cause of syringomyelia.